1988
DOI: 10.1002/bjs.1800751020
|View full text |Cite
|
Sign up to set email alerts
|

Abdominoperineal and anterior resection of the rectum with retrocolic omentoplasty and no drainage

Abstract: Forty consecutive patients scheduled for either low anterior resection or abdominoperineal resection of the rectum have been studied. After standard procedures, carried out by all grades of surgeons, the omentum was mobilized as a pedicle graft based on the left gastro-epiploic arcade and transposed to the pelvis or perineum. All wound were closed primarily without drainage. Twenty-six patients had anterior resection, 11 abdominoperineal resection and 3 an extended Hartmann's operation. Patients were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…13,15,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Seven publications were excluded because fewer than ten patients were included. 13,15,29,32,34,41,42 In addition, outcomes for patients in whom an omentoplasty was performed were not specified in two reports, and they were excluded.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…13,15,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Seven publications were excluded because fewer than ten patients were included. 13,15,29,32,34,41,42 In addition, outcomes for patients in whom an omentoplasty was performed were not specified in two reports, and they were excluded.…”
Section: Search Resultsmentioning
confidence: 99%
“…37,40 Evaluation of control groups in the other two studies was difficult because reported parameters for comparison were few in one study, 39 and one study used historical controls. 36 In four publications, data were collected prospectively, 30,33,36,40 and six were retrospective studies. 23,28,[37][38][39]43 Patients reported in one publication 33 also may have been reported in another.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An omental pedicle flap based on the left gastroepiploic vessels is left free or sutured into place in the pelvis. Alternatively, an omentopexy is performed using the omentum as a ''hammock,'' suturing the omental free edges to the sacral promontory, anterior abdominal wall and colon serosa [13][14][15][16][17][18][19][20][21][22][23][24][25]. Despite the extensive use of autologous tissues, especially the greater omentum, for creating a pelvic partition, there is no solid scientific evidence to support the use of one method over another.…”
Section: Discussionmentioning
confidence: 99%